Determinan Kinerja Auditor : Survey pada Auditor di Kantor Akuntan Publik - Teri (Insan Cita Bongaya Research Journal, 2024)
This study aims to analyze audit structure and job satisfaction in determining auditor performance. The survey was conducted on auditors who work at Public Accounting Firms in Makassar City. Data collection using questionnaire techniques and samepl extraction techniques is a saturated sampling technique. The number of samples taken was 33 respondents. The data analysis method uses multiple linear regression techniques. The results of the study show that audit structure and job satisfaction have a significant positive effect on auditor performance.